Perbedaan Pemberian Bioaktivator dalam Kompos Takakura terhadap Pertumbuhan Tanaman Tomat (Lycopersicum esculentum) - Agustin, Anjali Putri; Puspikawati, Septa Indra; Fatah, Mohammad Zainal (Preventia: The Indonesian Journal of Public Health, 2022)
Indonesia's population is increasing from year to year which has an impact on increasing the amount of waste and has a negative impact on public health and the environment. One of the proper waste handling methods is simple, practical, and efficient composting using the Takakura composting method. This study aims to determine the differences in stem height and number of leaves of tomato plants (Lycopersicum esculentum) between the control group and the treatment group with the addition of 4 bioactivators in Takakura compost. The research method uses an experimental design conducted in Banyuwangi during March-April 2022. Statistical analysis using T-test on data that is normally distributed and the Mann-Whitney test is used on data that is not normally distributed was carried out to determine differences in stem height and number of leaves of tomato plants (Lycopersicum esculentum). The results of this study showed that there was a difference (p value is 0.008 is less than 0.05) between the stem height of the tomato plants in the control and treatment groups with the addition of leachate activator compost, and there was no difference in the height of the tomato plants with the addition of EM4 bioactivator, BSF larvae, and drops. sugarcane. The results also showed no difference in the number of leaves from the addition of all bioactivators (EM4, BSF larvae, leachate, and molasses) in Takakura compost. It is recommended that further research be able to measure the C over N ratio during composting to determine the nutrient content in each activator during composting.